An Update of Recent Use of Aegilops Species in Wheat Breeding - Kishii, Masahiro (Frontiers in Plant Science, 2019)
Aegilops species has been significantly contributing to wheat breeding despite of the difficulties involved in the handling of wild species, such as cross ability and incompatibility. The number of biotic resistance genes have been identified and incorporated in wheat varieties from Aegilops species, and it is also contributing on complex traits such as yield and abiotic tolerance of drought and heat. The D genome diploid species of Aegilops tauschii has been utilized more in wheat breeding programs. Other Aegilops species are more difficult to utilize in the breeding because of less meiotic recombination frequency; generally it can be utilized in a form of translocation/introgression lines. After the emergence of Ug99 stem rust and Wheat Blast threat, Aegilops species gathered more attention as a form of new resistance sources. This article aims to update recent progress on the Aegilops species, as well as to cover new topics around its use in wheat breeding.